Up and Down States in Striatal Medium Spiny Neurons Simultaneously Recorded with Spontaneous Activity in Fast-Spiking Interneurons Studied in Cortex–Striatum–Substantia Nigra Organotypic Cultures - Plenz, Dietmar (J Neurosci, 1998)
In vivo intracellular spontaneous activity in striatal medium spiny (MS) projection neurons is characterized by “up” and “down” states. How this type of activity relates to the neuronal activity of striatal fast-spiking (FS) interneurons was examined in the presence of nigral and cortical inputs using cortex–striatum–substantia nigra organotypic cultures grown for 45 ± 4 d. The nigrostriatal projection was confirmed by tyrosine hydroxylase immunoreactivity. Corticostriatal (CS) projection neurons, striatal MS neurons, and FS neurons were intracellularly recorded and morphologically and electrophysiologically characterized. Intracellular spontaneous activity in the cultures consisted of intermittent depolarized periods of 0.5–1 sec duration. Spontaneous depolarizations in MS neurons were restricted to a narrow membrane potential range (up state) during which they occasionally fired single spikes. These up states were completely blocked by the glutamate antagonist CNQX. In FS interneurons, depolarized periods were characterized by large membrane potential fluctuations that occupied a wide range between rest and spike threshold. Also, FS interneurons spontaneously fired at much higher rates than did MS neurons. Simultaneous intracellular recordings established that during spontaneous depolarizations MS neurons and FS interneurons displayed correlated subthreshold neuronal activity in the low frequency range. These results indicate that (1) the CS projection neurons, striatal MS neurons, and FS interneurons grown in cortex–striatum–substantia nigra organotypic cultures show morphological and electrophysiological characteristics similar to those seen in vivo; (2) striatal MS neurons but not FS interneurons show an up state; (3) striatal MS neurons and FS interneurons receive common, presumably cortical inputs in the low frequency range. Our results support the view that the cortex provides a feedforward inhibition of MS neuron activity during the up state via FS interneurons.